Perancangan Sistem Smart Home Berbasis IoT Menggunakan ESP32 dan Aplikasi Blynk untuk Otomatisasi Perangkat Rumah Tangga - Rahayu, Poppy; Sularno, Sularno; Sari, Intan Utna (Jurnal Sistem Informasi Dan Informatika, 2025)
This study aims to design and implement an Internet of Things (IoT)-based smart home system capable of controlling household devices using an ESP32 module and the Blynk application. The background of this research is the need for an efficient, practical, and remote-accessible home automation system. The methodology follows the Extreme Programming (XP) model, covering planning, design, coding, and testing stages. The implementation results demonstrate that the system can control devices such as lights, fans, and water pumps via smartphone in real-time. The system also shows high operational efficiency and user-friendliness. This research contributes to the advancement of smart home technology by providing an economical and easy-to-implement solution. Keywords: Smart Home; Internet of Things; ESP32; Blynk; Automation.